Future security of the global Arctic state policy, economic security, and climate - Heininen, Lassi (Palgrave Macmillan, 2016)
"The post-Cold War Arctic has seen a transformation from military tension and a focus on national security to a concern for environmental and human security. As a result of this, the globalized Arctic has a high level of peace and stability, maintained by international cooperation between the Arctic states, northern indigenous peoples, sub-national governments and local actors. There has also been a shift from environmental protection to economic activities and, consequently, states easily trump other interests. Now, in the Arctic, these challenges require fresh thinking on a local and global scale. Regional wars, the 'war on terror', and economic crises have posed new threats to Northern security order. "...
Includes index
Keywords: POLITICAL SCIENCE / Political Freedom & Security / International Security; POLITICAL SCIENCE / Globalization; POLITICAL SCIENCE / Government / International; Globalisierung; Security, International -- Arctic regions; Militärpolitik; Umweltschutz; Menschliche Sicherheit; Arctic regions -- Strategic aspects; Arktis; Aufsatzsammlung